Pengaruh Konseling Kognitif Behavior dengan Teknik Self Management terhadap Prokrastinasi Akademik Siswa di SMAN 4 Payakumbuh - Salsabil Dwi Mahandi; Fadhilla Yusri (Lembaga Yasin AlSys, 2026)
Academic procrastination among Grade X students at SMAN 4 Payakumbuh remained relatively high, as indicated by the tendency to delay completing assignments, submit assignments late, and demonstrate a limited ability to manage study time. This study aimed to analyze the effect of cognitive-behavioral counseling using the self-management technique on students’ academic procrastination. The study employed a quantitative approach using a pre-experimental method and a one-group pretest–posttest design. The research sample consisted of eight students selected through purposive sampling. Data were collected using an academic procrastination questionnaire that met the validity and reliability criteria and were subsequently analyzed using the Wilcoxon signed-rank test. The results showed that the mean academic procrastination score decreased from 108.50 before the intervention to 49.75 after the intervention. The hypothesis test yielded an Asymp. Sig. (2-tailed) value of 0.012 < 0.05, indicating a significant difference between the levels of academic procrastination before and after the intervention. Thus, cognitive-behavioral counseling using the self-management technique was effective in reducing academic procrastination among Grade X students at SMAN 4 Payakumbuh. These findings provide practical implications for Guidance and Counseling teachers in implementing this service as an alternative intervention to improve students’ self-management abilities and reduce the tendency to delay academic tasks.